Understanding Genetic Regulation of Sex Differentiation in Hermaphroditic Fish - Junchao Fang; Guanglve Li; Wenyin Luo; Qiaomu Hu (Animals)
As a fundamental taxonomic group within vertebrates, fish represent an invaluable resource for investigating the mechanisms underlying sex determination and differentiation owing to their extensive geographical distribution and rich biodiversity. Within this biological cohort, the processes of sex determination and differentiation are intricately governed by both genetic factors and the complex interplay of environmental cues. While variations in external environmental factors, particularly temperature, can exert a modulatory influence on sex differentiation in fish to a limited degree, genetic factors remain the primary determinants of sexual traits. Hermaphroditic fish display three distinct types of sexual transitions: protandry (male to female), protogyny (female-to-male), bidirectional sex change (both directions serially). These fish, characterized by their unique reproductive strategies and sexual plasticity, serve as exemplary natural models for elucidating the mechanisms of sex differentiation and sexual transitions in fish. The present review delves into the histological dynamics during gonadal development across three types of sequential hermaphroditic fish, meticulously delineating the pivotal characteristics at each stage, from the inception of primordial gonads to sexual specialization. Furthermore, it examines the regulatory genes and associated signaling pathways that orchestrate sex determination and differentiation. By systematically synthesizing these research advancements, this paper endeavors to offer a comprehensive and profound insight into the intricate mechanisms governing sex differentiation in sequential hermaphroditic fish.